PROPOSALS OF MINERAL METABOLIC DISORDERS OF COWS IN THE AREA OF THE ISLANDERY (Web of Technology: Multidimensional Research Journal, 2025)
This article provides information on metamine disorders of vitamin-mineral metal disorders as a result of micronutrient deficiency in the Aral Sea cows. In addition, the blood contains insufficiency of elements, their group treatment and prevention.